The stability loss of a locally curved double-walled carbon nanotube in visco-elastic matrix - Coban Kayikci, Fatma; Kosker, Resat (SAGE PUBLICATIONS LTD, 2022)
In the current study, stability loss investigation is carried out for a viscoelastic medium containing a double-walled carbon nanotube with local curvature. This research has been carried out using the three dimensional linearized stability theory (TDLTS) within the framework of the piecewise-homogeneous body model. In this case, it is supposed that the carbon nanotube (CNT) has an insignificant initial local defect, and the increase of this defect with the flow of time is examined. Moreover, it is accepted as the criterion for determining the loss of stability that local curvature of the CNT starts to grow indefinitely. The values of the critical time and critical force are obtained from this criterion. In addition, van der Waals forces between the inner surface of the outer tube of the CNT and the outer surface of the inner tube of the CNT were considered. The fractional-exponential Rabotnov operator defines the composite material's viscoelasticity properties. It is expected that the results obtained from this paper may be a useful guide in applications related to exhibiting the mechanical behavior of the composite material under consideration. Therefore, the effects of viscoelasticity towards composite materials containing a locally curved DWCNT and the limits to be considered in the production of this material are obtained.
Keywords: Carbon nanotubes; stability loss; local curvature; CIRCULAR HOLLOW CYLINDER; 3D ANALYSES; COMPOSITES; Engineering